Analysis of Islamic Education Teachers' Ability in Utilizing Multimedia in the Digital Classroom of MTsN 1 Lhokseumawe City in the Subject of Aqidah Akhlak - Muhammad Fadel Samsuri (Penerbit Hellow Pustaka, 2025)
This research is motivated by the changing educational paradigm that increasingly leads to the use of digital technology in the learning process. Teachers have a central role in developing and implementing multimedia to improve learning effectiveness, especially in the subject of Aqidah Akhlak which requires in-depth understanding. This study used a qualitative descriptive approach with observation, interview, and documentation techniques, involving teachers, madrasah principals, and students at MTsN 1 Lhokseumawe City. The results showed that teachers' ability to utilize multimedia is quite good, with the use of media such as PowerPoint, video, Quizizz, and Google Classroom. However, there are still obstacles in the creativity of media development, limited training, and uneven motivation. The use of multimedia has been proven to increase student interest, engagement, and understanding, so it is recommended to improve teacher training and develop more interesting and contextual media.